Smart Home System Based on GSM Network - Karim, Bakhtiar Ali; Awl, halgurd Nawzad (Kurdistan Journal of Applied Research, 2018)
Due to increasing robbery and intrusion, establishing home-security system has become a correlated part of the modern houses, buildings, and offices. As the family members are not at home all the time, the traditional home security system, which makes alarm sound only, may not be efficient enough. Alternatively, Global System for Mobile communications (GSM) based security system can provide higher level of security and convenience compared to the traditionally used systems. The main objective of the current paper is to design and implement cost-efficient and reliable security, safety and home automation system for protection and occupants’ convenience. If any undesired events, such as intrusion, gas leakage and fire occurs in the house, our system warns the homeowner in real-time using Short Message Service (SMS). With the proposed system home appliances can also be controlled in three ways, namely sending SMS from the authorized numbers to the system through GSM network, smartphone app using Bluetooth module and infrared (IR) control using IR module